Safflower seed supplementation in lamb feed: effects upon fatty acid profile and quality of meat patty formulations - OLIVEIRA,MITALLY RAYANA C. DE (2021)
Abstract The aims of this study were to determine the fatty acid profile of meat from lambs fed with different levels of safflower seed (0%, 7.5%, and 15%) and, also, to compare the characteristics of the meat patties prepared from this lamb meat (LMP) with beef meat patties (BMP). The safflower seed-supplemented diet did not change the contents of polyunsaturated and unsaturated fatty acids, except for C22:1. All meat patty formulations were considered safe for consumption. The values of cooking yield, shrinkage, water absorption index, luminosity (L*), and redness (a*) were similar for the LMP and BMP tested. While the safflower seed-supplemented diet did not alter the moisture, ash, and protein levels of LMP, the lipid content was lower than that in BMP. The incorporation of 15% safflower seed into lamb feed contributed to promoting better sensory attributes of the meat patties. Most of the physicochemical properties evaluated were similar among LMP and BMP. However, to improve the sensory properties of the product, dietary supplementation with 15% safflower seed is recommended.